The Booksellers' Bill 1774 legislating in the 18th century : a view from Sir Henry Cavendish's parliamentary diary - Johnson, Phillip (Wiley for the Parliamentary History Yearbook Trust, 2022)
"The history of copyright and publishing in the 18th century is well trodden, and an event in 1774 is one of the most explored of all. The house of lords heard the infamous case of Donaldson v Beckett in February, when it was found that copyright in printed books was by then a purely statutory creation. The case had attracted great public interest, as did the subsequent petition by the London Booksellers for a bill that would have delayed the full impact of the judgment for over a decade. The Booksellers’ Bill is used here as a window into how the public interacted with parliament, how it then legislated and how its work was viewed. This examination is possible because the debates on the Bill were recorded by Sir Henry Cavendish in shorthand, and his diary entries noting the relevant speeches are published here for the first time. Along with this invaluable record there remains in existence a substantial number of the lobbying papers as well as the extensive recording of the Bill proceedings in contemporary newspapers. All of these are reproduced here. So while the Bill was neither championed by the government nor part of any wider political picture, it was hard and bitterly fought and the materials available present to us a microcosm of parliamentary activity in the period in a way that was not to be possible again for decades."
Keywords: Großbritannien -- Parliament; Geschichte 1774; Geschichte 1700-1800; Gesetzgebung; Tagebuch; Abgeordneter; Cavendish, Henry / (1732-1804 / Sir) / Diaries; Great Britain / Parliament / History / 18th century; Booksellers and bookselling / Great Britain / History / 18th century; Copyright / Great Britain / History / 18th century; Cavendish, Henry / Sir / 1732-1804; Quelle